IMPLEMENTATION OF SNI 6729: 2016 IN ORGANIC RICE CULTIVATION AND FINANCIAL FEASIBILITY ANALYSIS - SURTI SURYA DINANTI; Nofrianil; John Nefri (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2022)
This can happen because only organic farmers cultivate rice organically, and only they can meet the needs of organic rice based on having an organic certificate from the LSO with the standar SNI 6729: 2016 on organic farming system.The purpose of this study is (1) describe the application of organic rice cultivation standards in the Lareh Sago Halaban subdistrict (2) analyze the financial feasibility of organic rice farming in the Lareh Sago Halaban sub-district. The study was conducted in March – April 2022 at Lareh Sago Halaban sub-disctrict. The sampling technique is purposive sampling with data analysis income and business feasibility. The result of the research is that organic farmers carry out the cultivation processes in accordance with SNI 6729: 2016 concerning organic farming system, ranging from mechanical land processing, the use organic seeds, the use of fertilizers, and pest control without chemicals, to the harvesting process. But they do not carry out the post-harvest process due to limited facilities and infrastructure for rice milling and earn an income of Rp. 1.151.827/planting season with BEP obtained of Rp. 2.887,179/planting season, production 502 kg, price Rp. 3.719/kg. R/C ratio 1.57 with a again of 0.57. So organic rice farming in the Lareh Sago Halaban sub-district is feasible and the probability or profit obtained is 57%.